Program intervensi pencegahan penyalahgunaan narkotika di Indonesia: A literature review - Febriyaningsih, Laeli; Intiasari, Arih Diyaning; Gamelia, Elviera (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Drug abuse among adolescents in Indonesia remains a serious public health issue. In response to this phenomenon, the government has implemented various forms of preventive interventions, such as mandatory rehabilitation programs, school counseling activities, and the involvement of religious institutions in anti-drug campaigns. Purpose: To review drug abuse prevention intervention programs in Indonesia. Method: This systematic literature review (SLR) examined seven primary articles published between 2015 and 2025, analyzed from Google Scholar, Scopus, PubMed, and ResearchGate. Results: The most common interventions were peer education in schools, community cadre training, and culture-based approaches. All programs demonstrated significant increases in knowledge and decreases in risky behaviors (p < 0.05). Internal factors such as participatory methods and contextual delivery contributed to success, while external challenges included social stigma and lack of family support. Conclusion: The most common and effective drug abuse prevention intervention in Indonesia is school-based education programs. The success of the program depends heavily on contextual delivery methods, active participant engagement, and supportive social environments. However, challenges such as stigma, lack of participation, and structural barriers remain limiting factors, necessitating adaptive, participatory, and community-based interventions to ensure the sustainability of their impact. Keywords: Abuse; Narcotics; Preventio. Pendahuluan: Penyalahgunaan narkotika di kalangan remaja di Indonesia masih menjadi isu kesehatan masyarakat yang serius. Sebagai bentuk tanggapan terhadap fenomena ini, pemerintah telah menerapkan berbagai bentuk intervensi pencegahan, seperti program rehabilitasi wajib, kegiatan penyuluhan di lingkungan sekolah, serta pelibatan lembaga keagamaan dalam kampanye anti narkoba. Tujuan: Untuk meninjau program intervensi pencegahan penyalahgunaan narkotika di Indonesia. Metode: Penelitian systematic literature review (SLR) yang meninjau tujuh artikel primer terbitan tahun 2015–2025, dianalisis dari Google Scholar, Scopus, PubMed, dan ResearchGate. Hasil: Intervensi yang paling umum adalah edukasi teman sebaya di sekolah, pelatihan kader komunitas, dan pendekatan berbasis budaya. Seluruh program menunjukkan peningkatan pengetahuan dan penurunan perilaku berisiko secara signifikan (p < 0.05). Faktor internal seperti metode partisipatif dan penyampaian kontekstual mendukung keberhasilan, sedangkan tantangan eksternal mencakup stigma sosial dan minimnya dukungan keluarga. Simpulan: Intervensi pencegahan penyalahgunaan narkotika yang paling umum dan efektif di Indonesia adalah program edukasi berbasis sekolah. Keberhasilan program sangat bergantung pada metode penyampaian yang kontekstual, keterlibatan aktif peserta, dan dukungan lingkungan sosial. Namun, tantangan seperti stigma, kurangnya partisipasi, dan hambatan struktural masih menjadi faktor penghambat, sehingga diperlukan intervensi yang adaptif, partisipatif, dan berbasis komunitas untuk memastikan keberlanjutan dampaknya. Kata Kunci: Narkotika; Pencegahan; Penyalahgunaan.